SITAMPAN: Mobile application for planting and harvesting of horticultural crops in Garut Regency - Soegoto, Eddy Soeryanto; Warlina, Lia; Supatmi, Sri; Rafdhi, Agis Abhi; Jumansyah, Rizky; Saputra, Herry (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2022)
Garut Regency’s agriculture sector has the most impact on the region’s GDP compared to other sectors. The Central Statistics Agency reports that the agricultural sector’s contribution was 39.11% in 2014 and will be 37.97% in 2020. The farmer’s inability to manage their crop goods is the primary cause of the contribution decline. The study aims to build a prototype of a mobile application information system for planting and harvesting. commodities based on a geospatial information system. The research method used was field surveys, interviews, and focus group discussions (FGD) with farmers, farmer group leaders, agricultural extension workers, and officials at Garut Regency Agriculture Office. The designed application is Sitampan which stands for Sistem Informasi Tanam dan Panen (Planting and Harvesting Information System). The users of this application are farmers, farmer group leaders, agricultural extension workers, and Garut Regency Agriculture Office. Each user will have a specific role and access based on their roles. The public can only see the data contained in this application. In conclusion, this app can serve as a platform for information and communication for farmers. Farmers can use this app as a decision-making tool to manage their crops, including when to sell, plant, and harvest. Hopefully, this application will enhance the welfare of farmers, particularly those in Garut district, one of the industries that have the most impact on the Indonesian agricultural sector.